1978
DOI: 10.1111/j.1095-8649.1978.tb03448.x
|View full text |Cite
|
Sign up to set email alerts
|

Some histopathological effects of Aroclor 1254 on the liver and gonads of rainbow trout, Salmo gairdneri and carp, Cyprinus carpio

Abstract: Sexually mature and 9 rainbow trout (Salmo gairdneri Richardson) and carp (Cyprinus carpio L.) were injected intraperitoneally with Aroclor 1254 (25 mg kg-' body weight in 1 ml of arachis oil) once weekly for four weeks. Arachis oil was used as the control. At the end of the fourth week, samples of the liver, testis and ovary were taken from treated and control fish and examined by light and electron microscopy. The light microscope study indicated that there was general vacuolation of the hepatocytes of trout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 12 publications
3
8
0
Order By: Relevance
“…The cell organization observed in control barbel hepatocytes is classic and quite comparable to that observed in other fish hepatocytes (e.g., Hacking et al, 1977;Sivarajah et al, 1978;Ko¨hler, 1990). The absence of SER and Golgi apparatus has also been noted previously (Chapman, 1981) in rainbow trout.…”
Section: Liver Ultrastructuresupporting
confidence: 85%
“…The cell organization observed in control barbel hepatocytes is classic and quite comparable to that observed in other fish hepatocytes (e.g., Hacking et al, 1977;Sivarajah et al, 1978;Ko¨hler, 1990). The absence of SER and Golgi apparatus has also been noted previously (Chapman, 1981) in rainbow trout.…”
Section: Liver Ultrastructuresupporting
confidence: 85%
“…Median concentrations of E2 in male and female carp were inversely correlated with sediment PCB residues in Woods Pond, Massachusetts (Smith et al, 2002). Antiandrogenic and PCBs, HG, and endocrine disruption in Hudson fish antiestrogenic effects were observed in carp after four weeks of intraperitoneal injections of Aroclor 1254; concentrations of estrogens and androgens in blood of female and male were significantly reduced (Sivarajah et al, 1978a); developing oocytes became fragmented and spermatozoa were damaged (Sivarajah et al, 1978b).…”
Section: Relation Of Endocrine Biomarkers To Pcb Residuesmentioning
confidence: 99%
“…At 0.032 and 0.064 ppm of diazinon, karyolysis and fragmented ovary and testis with abnormal shape and arrangement were observed which agreed with the findings of Hossain et al (2002). Sivarajah et al (1978) also reported similar type of fragmentation and karyolysis in the ovaries of Salmo gairdneri and Cyprinus carpio when exposed to the organochlorine pesticide, Aroclor. The liver of G. giuris in the control was normal without necrosis, hepatocytes and other cells were normal and systematically arranged.…”
Section: Discussionmentioning
confidence: 70%